Electrolyte and preparation process of ultrahigh-tensile electrolytic copper foil
By adding specific additives to the electrolyte of lithium-ion batteries and optimizing the electrolytic process, electrolytic copper foils with ultra-high tensile strength and good ductility are prepared, which solves the problem of insufficient tensile strength of copper foils in the prior art and improves the safety and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411735992.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery copper foil preparation, and in particular to an electrolyte and a preparation process of ultra-high tensile strength electrolytic copper foil. Background Art
[0002] Electrolytic copper foil has become one of the indispensable key materials in the manufacture of copper-clad laminates, printed circuit boards and lithium-ion batteries due to its high conductivity, excellent mechanical properties and good processability. With the advancement of electronic equipment and battery technology, the demand for electrolytic copper foil is also increasing, driving the technological development and application innovation of this material in various fields.
[0003] Application No. CN202010112680.1 discloses additives for high tensile electrolytic copper foil and a process for preparing high tensile electrolytic copper foil. The tensile strength of the electrolytic copper foil is improved by adding 5-10 g / L of collagen per liter of aqueous solution A, 1-8 g / L of sodium 3-mercapto-1-propanesulfonate and / or sodium dimethyl-dithiocarbonylpropane sulfonate per liter of aqueous solution B, and 1-10 g / L of sodium 2-mercaptobenzoimidazolepropane sulfonate and 5-20 g / L of hydroxyethyl cellulose per liter of aqueous solution C. The product is better controlled during production, and the tensile strength of the electrolytic copper foil produced is greater than 450 MPa.
[0004] However, due to the requirements of lithium-ion batteries for high performance and long life, higher requirements are placed on copper foil, especially in terms of tensile strength. As the negative electrode current collector of lithium-ion batteries, high-tensile copper foil can support the design of higher energy density batteries, can withstand high pressure and current density inside the battery, while maintaining its structural stability and not prone to deformation or breakage. In addition, high-tensile-strength copper foil can effectively reduce the risk of thermal expansion of the battery during rapid charging and discharging, improve the safety and stability of the battery, and reduce these potential risks. High-tensile copper foil also plays a role in reducing the loss of the battery due to material fatigue during long-term use and extending the service life of the battery. Therefore, there is an urgent need for a copper foil with ultra-high tensile strength. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention discloses an electrolyte, which is used to prepare an electrolytic copper foil having good physical and mechanical properties, high tensile strength and good ductility.
[0006] To achieve the above technical objectives, the technical solution of the present invention is implemented as follows: An electrolyte, comprising a main electrolyte and an additive, wherein the main electrolyte comprises copper sulfate, sulfuric acid and chloride ions, wherein the additive comprises an agent A, an agent B, an agent C and an agent D, wherein the agent A is a wetting agent, the agent B is a leveling agent, the agent C is a brightener, and the agent D is a stress relieving agent; The agent A wetting agent is selected from one or a mixture of the following: hydroxyethyl cellulose, sulfonated hydroxyethyl cellulose, quaternized hydroxyethyl cellulose; The B-agent leveler is a mixture of collagen and polyethyleneimine alkyl compound, wherein the molecular weight of the collagen is 3000-12000Da; The C-agent brightener is selected from one or a mixture of the following: sodium thiazoline dithiopropane sulfonate and hexylbenzyl ammonium salt; The agent D stress reliever is selected from one or a mixture of the following: fatty amine ethoxy sulfonate and N-(3-sulfopropyl)-saccharin sodium salt.
[0007] Furthermore, the content of the B-agent leveler is 10-30 mg / L.
[0008] Furthermore, the content of the stress reliever in agent D is 3-15 mg / L.
[0009] Furthermore, the contents of copper ions, sulfuric acid, chloride ions, agent A, agent B, agent C and agent D in the electrolyte are 70-90 g / L, 80-100 g / L, 25-40 mg / L, 2.5-10 mg / L, 10-30 mg / L, 5-15 mg / L and 3-15 mg / L, respectively.
[0010] Furthermore, the contents of the copper ion, sulfuric acid, chloride ion, agent A, agent B, agent C and agent D are 90g / L, 80g / L, 35mg / L, 10mg / L, 15mg / L, 10mg / L and 10mg / L, respectively.
[0011] Furthermore, the wetting agent A is selected from hydroxyethyl cellulose: 5 mg / L, quaternized hydroxyethyl cellulose: 5 mg / L, and the total amount of the two is 10 mg / L; The B-leveling agent is selected from collagen with a number average molecular weight of 3000 Da: 7.5 mg / L, polyethyleneimine alkyl compound: 7.5 mg / L, the total of the two is 15 mg / L; The brightener C is composed of 5 mg / L sodium thiazoline dithiopropane sulfonate and 5 mg / L hexylbenzyl ammonium salt, the total of which is 10 mg / L. The D-agent stress reliever is selected from fatty amine ethoxy sulfonate: 10 mg / L.
[0012] On the other hand, we prepared ultra-high tensile strength electrolytic copper foil based on the above electrolyte, and the preparation process is as follows: Step 1: prepare the above electrolyte, and electrolyze the electrode plates in an electrolytic cell; Step 2: Anti-oxidation treatment, water washing and drying of the electrolytic copper foil on the plate; Step 3: Peeling the electrolytic copper foil from the electrode plate and performing annealing treatment to obtain an ultra-high tensile strength electrolytic copper foil.
[0013] Furthermore, the anti-oxidation treatment in step 2 is a chromic anhydride aqueous solution treatment; in the chromic anhydride aqueous solution, the concentration of hexavalent chromium ions is 0.9-1.3 g / L, and the concentration of phosphate ions is 1.0-1.5 g / L; the pH value of the chromic anhydride aqueous solution is <3, and the temperature is 20-40°C.
[0014] Furthermore, the annealing treatment in step three is performed at a temperature of 180-200° C. and for a time of 50-70 seconds.
[0015] Beneficial effects of the present invention: By adding agent B to the electrolyte, collagen and imine derivatives are used as leveling agents to promote the face-center growth of copper foil grains, make the copper grains dense, and generate great internal stress. At the same time, the ratio of electrolyte additives is optimized to prepare a denser copper foil.
[0016] The electrolytic copper foil prepared by the electrolyte of the present invention has a thickness of 6-8 μm, good physical and mechanical properties, and a tensile strength of more than 600 MPa, belonging to an ultra-high tensile electrolytic copper foil. At the same time, the ductility is good, and the elongation is more than 3%. DETAILED DESCRIPTION
[0017] The specific implementation method of the present invention is further described below in conjunction with examples. It should be noted here that the specific implementation method described here is only for illustrating and explaining the present invention and is not intended to limit the scope of protection of the present invention.
[0018] The following examples were prepared using conventional small-scale experiments in the field. The thickness of the prepared copper foil can be adjusted between 6-8 μm by controlling the current and the electroplating time. The small-scale experiment used a small electrolysis system, the amount of electrolyte added was 3L, and the area of the cathode and anode plates immersed in the electrolyte was 1.0 dm 2 , the plate distance is 1 cm, the rectifier current is 25-40A, the electroplating time is 49-78s, and the embodiments are as follows: Example 1 Prepare a main electrolyte with a copper ion concentration of 70g / L, a sulfuric acid content of 80g / L, and a chloride ion concentration of 25mg / L, pour it into a small electrolytic cell, and add an additive aqueous solution into the electrolytic cell and stir evenly to make the content in the electrolyte as follows: Hydroxyethyl cellulose: 5 mg / L; Collagen with a number average molecular weight of 12000 Da: 2.5 mg / L, polyethyleneimine alkyl compound: 7.5 mg / L, the total of the two is 10 mg / L; Sodium thiazoline dithiopropane sulfonate: 10 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 10 mg / L; The plates were electrolyzed at 48°C with a current density of 25A / dm 2 The electrolysis time is 78s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for oxidation protection, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0019] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0020] Example 2 Prepare a main electrolyte with a copper ion concentration of 70g / L, a sulfuric acid content of 85g / L, and a chloride ion concentration of 30mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 10 mg / L; Collagen with a number average molecular weight of 6000 Da: 6.67 mg / L, polyethyleneimine alkyl compound: 13.33 mg / L, the total of the two is 20 mg / L; Sodium thiazoline dithiopropane sulfonate: 15 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 5 mg / L; The plates were electrolyzed at 50°C with a current density of 25A / dm 2 The electrolysis time is 78s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for oxidation protection, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0021] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0022] Example 3 Prepare a main electrolyte with a copper ion concentration of 80g / L, a sulfuric acid content of 90g / L, and a chloride ion concentration of 35mg / L, pour it into a small electrolytic cell, and add an additive aqueous solution into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 2.5 mg / L; Collagen with a number average molecular weight of 3000 Da: 15 mg / L, polyethyleneimine alkyl compound: 15 mg / L, the total of the two is 30 mg / L; Sodium thiazoline dithiopropane sulfonate: 10 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 5 mg / L; The plates were electrolyzed at 52°C with a current density of 25A / dm 2 The electrolysis time is 78s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for oxidation protection, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0023] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0024] Example 4 Prepare a main electrolyte with a copper ion concentration of 70g / L, a sulfuric acid content of 80g / L, and a chloride ion concentration of 25mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 2.5 mg / L, sulfonated hydroxyethyl cellulose: 2.5 mg / L, the total of the two is 5 mg / L; Collagen with a number average molecular weight of 3000 Da: 7.5 mg / L, polyethyleneimine alkyl compound: 7.5 mg / L, the total of the two is 15 mg / L; Sodium thiazoline dithiopropane sulfonate: 5 mg / L, hexylbenzyl ammonium salt: 5 mg / L, the total of the two is 10 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 5 mg / L; The plates were electrolyzed at 48°C with a current density of 30A / dm 2 The electrolysis time is 65s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0025] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0026] Example 5 Prepare a main electrolyte with a copper ion concentration of 85g / L, a sulfuric acid content of 95g / L, and a chloride ion concentration of 25mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 5 mg / L, sulfonated hydroxyethyl cellulose: 5 mg / L, the total of the two is 10 mg / L; Collagen with a number average molecular weight of 3000 Da: 12.5 mg / L, polyethyleneimine alkyl compound: 12.5 mg / L, the total of the two is 25 mg / L; Sodium thiazoline dithiopropane sulfonate: 7.5 mg / L, hexylbenzyl ammonium salt: 7.5 mg / L, the total of the two is 15 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 10 mg / L; The plate was electrolyzed at 50°C with a current density of 30A / dm 2 The electrolysis time is 65s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0027] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0028] Example 6 Prepare a main electrolyte with a copper ion concentration of 80 g / L, a sulfuric acid content of 100 g / L, and a chloride ion concentration of 30 mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 5 mg / L, sulfonated hydroxyethyl cellulose: 5 mg / L, the total of the two is 10 mg / L; Collagen with a number average molecular weight of 3000 Da: 15 mg / L, polyethyleneimine alkyl compound: 15 mg / L, the total of the two is 30 mg / L; Sodium thiazoline dithiopropane sulfonate: 7.5 mg / L, hexylbenzyl ammonium salt: 7.5 mg / L, the total of the two is 15 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 15 mg / L; The plates were electrolyzed at 52°C with a current density of 30A / dm 2The electrolysis time is 65s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0029] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0030] Example 7 Prepare a main electrolyte with a copper ion concentration of 70g / L, a sulfuric acid content of 100g / L, and a chloride ion concentration of 25mg / L, pour it into a small electrolytic cell, and add an additive aqueous solution into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 2.5 mg / L, quaternized hydroxyethyl cellulose: 2.5 mg / L, the total of the two is 5 mg / L; Collagen with a number average molecular weight of 3000 Da: 5 mg / L, polyethyleneimine alkyl compound: 5 mg / L, the total of the two is 10 mg / L; Sodium thiazoline dithiopropane sulfonate: 7.5 mg / L, hexylbenzyl ammonium salt: 7.5 mg / L, the total of the two is 15 mg / L; Fatty amine ethoxylate: 5 mg / L; The plates were electrolyzed at 48°C with a current density of 35A / dm 2 The electrolysis time is 56s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0031] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0032] Example 8 Prepare a main electrolyte with a copper ion concentration of 90g / L, a sulfuric acid content of 80g / L, and a chloride ion concentration of 35mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 5 mg / L, quaternized hydroxyethyl cellulose: 5 mg / L, the total of the two is 10 mg / L; Collagen with a number average molecular weight of 3000 Da: 7.5 mg / L, polyethyleneimine alkyl compound: 7.5 mg / L, the total of the two is 15 mg / L; Sodium thiazoline dithiopropane sulfonate: 5 mg / L, hexylbenzyl ammonium salt: 5 mg / L, the total of the two is 10 mg / L; Fatty amine ethoxylate: 10 mg / L; The plate was electrolyzed at 52°C with a current density of 35A / dm 2 The electrolysis time is 56s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0033] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0034] Example 9 Prepare a main electrolyte with a copper ion concentration of 70g / L, a sulfuric acid content of 90g / L, and a chloride ion concentration of 30mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 5 mg / L, quaternized hydroxyethyl cellulose: 5 mg / L, the total of the two is 10 mg / L; Collagen with a number average molecular weight of 3000 Da: 15 mg / L, polyethyleneimine alkyl compound: 15 mg / L, the total of the two is 30 mg / L; Sodium thiazoline dithiopropane sulfonate: 5 mg / L, hexylbenzyl ammonium salt: 5 mg / L, the total of the two is 10 mg / L; Fatty amine ethoxylate: 15 mg / L; The plates were electrolyzed at 48°C with a current density of 40A / dm 2 The electrolysis time is 49s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0035] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0036] Example 10 Prepare a main electrolyte with a copper ion concentration of 80g / L, a sulfuric acid content of 80g / L, and a chloride ion concentration of 25mg / L, pour it into a small electrolytic cell, and add an additive aqueous solution into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 2.5 mg / L, quaternized hydroxyethyl cellulose: 2.5 mg / L, the total of the two is 5 mg / L; Collagen with a number average molecular weight of 3000 Da: 10 mg / L, polyethyleneimine alkyl compound: 10 mg / L, the total of the two is 20 mg / L; Sodium thiazoline dithiopropane sulfonate: 7.5 mg / L, hexylbenzyl ammonium salt: 7.5 mg / L, the total of the two is 15 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 2.5 mg / L, fatty amine ethoxy sulfonate: 2.5 mg / L, the total of the two is 5 mg / L; The plate was electrolyzed at 50°C with a current density of 40A / dm 2 The electrolysis time is 49s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0037] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0038] Embodiment 11 Prepare a main electrolyte with a copper ion concentration of 90g / L, a sulfuric acid content of 100g / L, and a chloride ion concentration of 35mg / L, pour it into a small electrolytic cell, and add an aqueous solution of additives into the electrolytic cell and stir evenly so that its content in the electrolyte is as follows: Hydroxyethyl cellulose: 5 mg / L, quaternized hydroxyethyl cellulose: 5 mg / L, the total of the two is 10 mg / L; Collagen with a number average molecular weight of 3000 Da: 7.5 mg / L, polyethyleneimine alkyl compound: 7.5 mg / L, the total of the two is 15 mg / L; Sodium thiazoline dithiopropane sulfonate: 5 mg / L, hexylbenzyl ammonium salt: 5 mg / L, the total of the two is 10 mg / L; N-(3-sulfopropyl)-saccharin sodium salt: 5 mg / L, fatty amine ethoxy sulfonate: 5 mg / L, the total of the two is 10 mg / L; The plate was electrolyzed at 52°C with a current density of 40A / dm 2The electrolysis time is 49s. The copper foil prepared by the above electrolysis process is treated with conventional chromic anhydride aqueous solution for anti-oxidation, and then washed and dried. After being peeled off from the electrode plate, it is annealed to obtain an ultra-high tensile electrolytic copper foil.
[0039] The concentration of hexavalent chromium ions in the chromic anhydride aqueous solution is 1 g / L, the concentration of phosphate ions is 1.2 g / L, the pH value of the chromic anhydride aqueous solution is 2.5, and the temperature is 30° C. The annealing temperature is 200° C. and the time is 60 s.
[0040] The basic physical properties of the electrolytic copper foil samples obtained in Examples 1-11 were tested, and the testing method was as follows: 1. Tensile / elongation performance test The tensile strength and elongation of copper foil were tested with reference to the method in Section 2.4.18 of the IPC-TM-650 Test Method Manual of the American Electronic Circuit and Interconnection Industry Association.
[0041] 2. Roughness test The roughness of the matte surface of the copper foil was tested with reference to the method in Section 2.4.15 of the IPC-TM-650 Test Method Manual of the American Electronic Circuit and Interconnection Industry Association.
[0042] The basic physical property data of the electrolytic copper foils prepared in Examples 1-11 are listed in Table 1 below.
[0043] Table 1 Basic physical properties of electrolytic copper foil As shown in Table 1, the present invention has a temperature of 48-52°C and a current density of 25-40A / dm 2 The thickness of the electrolytic copper foil prepared under the working conditions is 6-8μm, with good physical properties, and the tensile strength is above 600Mpa. Even the tensile strength in Example 8 reaches 680.70Mpa, which is an ultra-high tensile copper foil. The elongation is above 3% and has good density, and the surface roughness is low. It shows that the use of imide derivatives as additive B is of great help in the production of ultra-high tensile copper foil. The use of the above-mentioned electrolyte composition, additive ratio and electrolysis adjustment can obtain an ultra-high tensile copper foil that meets the conditions, and the prepared copper foil has good ductility.
[0044] The above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not used to limit the present invention. A technician in the technical field to which the present invention belongs can also make several simple deductions, deformations, substitutions or combinations based on the concept of the present invention. These deductions, deformations, substitutions or combinations also fall within the scope of the claims of the present invention.
Claims
1. An electrolyte comprising a main electrolyte and an additive, wherein the main electrolyte comprises copper sulfate, sulfuric acid and chloride ions, characterized in that The additives include agent A, agent B, agent C and agent D, agent A is a wetting agent, agent B is a leveling agent, agent C is a brightener, and agent D is a stress relieving agent; The agent A wetting agent is selected from one or a mixture of the following: hydroxyethyl cellulose, sulfonated hydroxyethyl cellulose, quaternized hydroxyethyl cellulose; The B-agent leveler is a mixture of collagen and polyethyleneimine alkyl compound, wherein the molecular weight of the collagen is 3000-12000Da; The C-agent brightener is selected from one or a mixture of the following: sodium thiazoline dithiopropane sulfonate and hexylbenzyl ammonium salt; The agent D stress reliever is selected from one or a mixture of the following: fatty amine ethoxy sulfonate and N-(3-sulfopropyl)-saccharin sodium salt.
2. An electrolyte according to claim 1, characterized in that: The content of the B-agent leveler is 10-30 mg / L.
3. An electrolyte according to claim 1, characterized in that: The content of the D stress reliever is 3-15 mg / L.
4. An electrolyte according to claim 1, characterized in that: The contents of the copper ion, sulfuric acid, chloride ion, agent A, agent B, agent C and agent D are 70-90 g / L, 80-100 g / L, 25-40 mg / L, 2.5-10 mg / L, 10-30 mg / L, 5-15 mg / L and 3-15 mg / L respectively.
5. An electrolyte according to claim 4, characterized in that: The contents of the copper ion, sulfuric acid, chloride ion, agent A, agent B, agent C and agent D are 90g / L, 80g / L, 35mg / L, 10mg / L, 15mg / L, 10mg / L and 10mg / L respectively.
6. An electrolyte according to claim 1, characterized in that: The wetting agent A is 5 mg / L hydroxyethyl cellulose and 5 mg / L quaternized hydroxyethyl cellulose, the total of which is 10 mg / L. The B-leveling agent is selected from collagen with a number average molecular weight of 3000 Da: 7.5 mg / L, polyethyleneimine alkyl compound: 7.5 mg / L, the total of the two is 15 mg / L; The brightener C is composed of 5 mg / L sodium thiazoline dithiopropane sulfonate and 5 mg / L hexylbenzyl ammonium salt, the total of which is 10 mg / L. The D-agent stress reliever is selected from fatty amine ethoxy sulfonate: 10 mg / L.
7. A process for preparing ultra-high tensile strength electrolytic copper foil, characterized in that: The following steps are involved: Step 1: preparing the electrolyte according to any one of claims 1 to 6, and electrolyzing the electrode plates in an electrolytic cell; Step 2: Anti-oxidation treatment, water washing and drying of the electrolytic copper foil on the plate; Step 3: Peeling the electrolytic copper foil from the electrode plate and performing annealing treatment to obtain an ultra-high tensile strength electrolytic copper foil.
8. The process for preparing the ultra-high tensile strength electrolytic copper foil according to claim 8, characterized in that: The anti-oxidation treatment in step 2 is a chromic anhydride aqueous solution treatment; in the chromic anhydride aqueous solution, the concentration of hexavalent chromium ions is 0.9-1.3 g / L, and the concentration of phosphate ions is 1.0-1.5 g / L; the pH value of the chromic anhydride aqueous solution is less than 3, and the temperature is 20-40°C.
9. The process for preparing the ultra-high tensile strength electrolytic copper foil according to claim 7, characterized in that: The temperature of the annealing treatment in step three is 180-200° C. and the time is 50-70 seconds.
Citation Information
Patent Citations
Addition agent for highly-tensile electrolytic copper foil and technology for preparing highly-tensile electrolytic copper foil
CN111270273A
Cited By
A composite electrolyte for low-stress lithium battery copper foil and a method for preparing low-stress lithium battery copper foil
CN122918656A